Raising CV. Petra Kharisma Abadi’s Brand Awareness to Its Target Market Using A New Logo, Brand Name, and Slogan - Karenina Gracia Pribadi (Institute of Research and Community Outreach - Petra Christian University, 2022)
CV. Petra Kharisma Abadi, now PeKA, is a company that makes and sells food-boxes in Magelang and Kedu areas. The customers are mainly from Magelang, 60% females 40% males, aged between 25 - 55 years. The main problem that I have found from the customer survey is lack of brand awareness, because the target customers cannot recognize the name of the company and its’ product. From the customer survey, I found that the solutions are making a new brand name, logo, and slogan. Besides, the company must highlight the USPs (durability, beauty, and low price). I used theories that focus on my main subjects, which are brand awareness, brand name, logo, and slogan. There are three benefits from the solution: target customers can be more familiar with the company, can boost sales by having the target market’s trust, and can later have a correct method of promotions after good branding.